Diseño ecoeficiente de hormigón con residuos de materiales de obra para elementos no estructurales - Trelles Puma, Edward Gabriel (2024)
In recent years, concrete has become an extremely broad and versatile architectural and decorative solution based on a specific construction material for large structures. The developments and innovations in its composition make concrete adding crushed concrete from demolitions of previous works contribute to reducing the amount of contamination, as well as costs in works. This new material is commonly directed toward landfills. Through this investigative project, we use recycled concrete generated by demolished buildings to form part of a new concrete design. For this we developed a traditional hydraulic concrete design with a compressive strength of f'c 210 Kg/cm², which we used its dosage to prepare the concrete mixture with crushed concrete. The mixture made with the innovative material such as recycled concrete was made in percentages of 10 and 20 percent with the weight of the granular material, the same percentages of sand, cement and water of the traditional design were maintained, seven cylinder intakes were made of concrete for each percentage and the compression test was carried out at 3, 7, 14, 21 and 28 days respectively, giving satisfactory results with the mixture with 10% of the crushed concrete, so that they can be used in low resistance elements.